2020
DOI: 10.1177/1350650120931979
|View full text |Cite
|
Sign up to set email alerts
|

Elasto-hydrodynamic analysis of journal bearing operating with nanolubricants

Abstract: In this study, performance parameters of a rigid and flexible journal bearing using non-Newtonian nanolubricants have been investigated and compared. Krieger-Dougherty viscosity model has been implemented with a non-Newtonian model (power law) to evaluate the effective viscosity of nanolubricants. In order to attain the pressure field of nanolubricants, a numerical solution of the modified Reynolds equation has been derived with initial assumptions and boundary conditions using finite difference method. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…This is due to the fact that the viscosity of the base lubricant increases with the addition of nanoparticles; consequently, the fluid film pressure increases. This result is supported by the study of Khan et al, 39 in which the generated maximum pressure within the lubricant film is highly influenced by the particle concentration, where the lubricant film pressure increased with an increase in the particle concentration. An appreciable increase in the hydrodynamic pressure is observed for the volume fraction of 0.02% in comparison with other volume fractions.…”
Section: Resultssupporting
confidence: 73%
“…This is due to the fact that the viscosity of the base lubricant increases with the addition of nanoparticles; consequently, the fluid film pressure increases. This result is supported by the study of Khan et al, 39 in which the generated maximum pressure within the lubricant film is highly influenced by the particle concentration, where the lubricant film pressure increased with an increase in the particle concentration. An appreciable increase in the hydrodynamic pressure is observed for the volume fraction of 0.02% in comparison with other volume fractions.…”
Section: Resultssupporting
confidence: 73%
“…Nanoparticle weight concentration has been converted to volume fraction of nanoparticles using the relationship given by Azmi et al [36] as given in Eq. (8).…”
Section: Nanolubricantsmentioning
confidence: 99%
“…With the advent of nanotechnology, nanoparticles have been explored as lubricant additives for overcoming the drawbacks of traditional antifriction/ antiwear additives [6]- [8]. Due to their small size, nanoparticles are capable of filling the small spaces between matching surfaces and impart special characteristics to the surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various authors have also evaluated the performance parameters of journal bearing theoretically operating under nano oil. 1317 Their results revealed that the oil containing nanoparticles significantly intensifies the bearing’s load capacity. The above-discussed studies clearly show that the adding of nanoadditives in base fluid improves the tribological characteristics of base fluid considerably to a great extent.…”
Section: Introductionmentioning
confidence: 99%